(untitled) (Medical Forum Monthly, 2020)
Objective: To study the laparoscopic findings in infertile females. Study Design: Descriptive cross sectional study Place and Duration of Study: This study was conducted at the Department of Obstetrics & Gynaecology, Lady Willingdon Hospital, Lahore from January 2018 to January 2020. Materials and Methods: One hundred and fifty patients with either primary or secondary infertility who underwent diagnostic laparoscopy and fulfilled the inclusion criteria were included. Results: The mean age of the participants was 32.15 ranging from 20 to 45 years. Mean age of the patients with primary infertility was 26.15 years and those with secondary infertility were 31.3 years of age. Amongst these females, 107 (71.3%) had primary infertility, whereas 43(28.6%) females had secondary infertility. Forty-seven (31.3%) cases turned out to have normal findings. Anomalous findings were noticed in 103 (68.7%) patients. Among the patients with abnormal findings, the leading cause of infertility was found to be tubal blockade which was seen in 40 (31.3%) cases. This was followed by endometriosis in 30 (29.1%) cases. The third leading cause in our study population was pelvic adhesions found in 28 (27.1%) cases. Polycystic ovarian disease was noticed in 3 (2.9%) and fibroid in 2 (1.9%) cases. Conclusion: The most common factor leading to infertility among females in our study was tubal blockade. This was followed by endometriosis, pelvic adhesions, PCOD and fibroids.